Surface Properties of Manganese(II) Carbonate - Nikolai V. Nikolenko; Irina M. Shapovalova (Adsorption Science & Technology)
The energies of unoccupied and occupied orbitals have been used as correlation parameters between the electronic and adsorptive properties of organic molecules. A model describing the chemisorption of organic compounds on MnCO 3 was proposed. This involves three types of interaction: 1-, 2- and 3-electron donor–acceptor interaction between adsorbent and adsorbate frontier orbitals.